79 Remote Delivery of an International Surgical Education Webinar Series for Medical Students During COVID-19. (12th October 2021) - Zaver, V; Ahari, D; Jayawardena, P; Sayed, M A
Abstract: Aim: The 2019 novel coronavirus (COVID-19) pandemic caused the cancellation of lectures and clinical placement-based education for medical students across the UK. With resumption of university teaching, remote delivery via online platforms has seen increased implementation to prevent overcrowding and comply with social distancing measures. This article explores the efficacy of an internationally delivered online surgical webinar series to facilitate undergraduate surgical education on a long-term basis. Method: The University of Manchester undergraduate surgical society, Scalpel, in collaboration with three Junior Surgical Trainees designed and organised an online surgical teaching programme aimed at medical students. The syllabus was constructed in accordance with the Royal College of Surgeons England's (RCSEng) National Undergraduate Curriculum in Surgery. Multiple-choice questionnaires (MCQs) were used to evaluate knowledge during the sessions and Likert scales were utilised to assess subjective improvement of knowledge. The teaching programme was delivered remotely using Zoom (Zoom Video Communications, Inc.). Results: he average attendance for the lectures was 68. The reach of the webinar series was international. The average increase in correct answers between pre and post lecture MCQs was +78.7% (+72.4, +18.6, +76.6, +43.5, +161, +100). Likert scale analysis demonstrated 100% improvement of knowledge. Conclusions: This study demonstrates a positive outcome to remote, extra-curricular surgical education in the time of COVID-19. The methodology outlined herein has the potential for easy replication on a more widespread scale to provide routine supplementation for medical student and surgical trainee education during the ongoing pandemic.